- The Correlation Between Insulin Resistance and Blood Lipids in Children : Correlation Between Insulin Resistance and Blood Lipids - xu, Xu Xu (Journal of Medical Biochemistry, 2024)
Abstract: Introduction: this work focused on correlation between insulin resistance (IR) and blood lipids (BL) in children with simple obesity as well as the intervention effects of high-intensity interval training (HIIT) in weight loss of children. Material and Method: 80 children aged 6 to 17 years with simple obesity were selected from our hospital and randomly grouped into two. Children in control (Ctrl) group underwent traditional moderate-intensity continuous training (MICT), while those in the other group received HIIT (HIIT group). After four weeks, body composition-related indicators, BL levels, and IR were measured. Results: after exercise, children in both groups possessed obvious reductions in body mass index (BMI), body fat percentage (BFP), triglyceride (TG), and homeostasis model assessment of IR (HOMA-IR), demonstrating remarkable differences in contrast to those after intervention (P<0.05). The HIIT group also exhibited considerable differences in waist circumference (WC), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) (P<0.05). After exercise, the HIIT group demonstrated more observable reductions in BMI, WC, TG, and HOMA-IR, showing great differences with Ctrl group (P<0.05). HOMA-IR exhibited positive correlations with TC, TG, and HDL-C but a negative one with LDL-C (P<0.05). Conclusion: HIIT improved the body composition and BL levels in children with simple obesity, downregulated HOMA-IR, and positively impacted their health status. Furthermore, IR was associated with BL-relevant indicators in children with simple obesity.